Relationship Between arm Span and Human Stature (Indian Journal of Forensic Medicine & Toxicology, 2025)
Background: Incomplete human remains may be recovered from crime scenes in some cases. Stature estimation from this remains may be very important in the personal identification of the corpse or living. If the stature could be estimated it can definitely narrow down the search in missing individual data base. This study was intended to find out correlation between arm span and human stature and to derive a regression model to find out human stature from arm span. Materials and methods: This cross sectional study was conducted on 100 subjects, 50 males and 50 females aged between 21 and 60 years in the department of Forensic Medicine in Govt. Medical College, Thrissur.  Results: In females the average arm span is 159.91±5.61cm, and mean height is 157.44±4.93cm, correlation coefficient (r) is 0.8388. In males the average arm span is 173.83±6.02 cm and mean height is 170.85±5.2cm, correlation coefficient (r) is 0.8934. Thus stature is strongly correlated with arm span.
Keywords: Stature, arm span, upper extremities, forensic anthropometry, identity